KOMPETENSI APARATUR PEMERINTAH DAERAH DALAM ERA REFORMASI - Budiman Sakti (PARETO : Jurnal Ekonomi dan Kebijakan Publik, 2019)
The implementation of the district/city government constitution in Indonesia during the "Era Reformasi" era placed the executive as a more dominant force than the legislature which caused frequent deviations from the regional government constitution. Applicability of Law No. 22 and 25 of 1999 were then renewed by law No. 23 of 2014, local governments, both regencies or cities, must increase human resources with professional knowledge and competencies to face the era of free trade by increasing the quality and competency of bureaucracy to reduce irregularities in district or city government institutions.